Characteristics of Soil Hydraulic Conductivity in Natural Forest, Agricultural Land, and Green Open Space Area (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Soil hydraulic conductivity is one of the important soil characteristics that determines the amount and proportion of water that will be infiltrated into the soil column and flowing as surface runoff. It is strongly influenced by soil porosity and soil characteristics that affect the soil porosity such as soil texture and structure and soil organic matter content (internally factors) as well as land management and the intensity of plant canopy cover (external factors). This research is aimed to identify the character of soil hydraulics conductivity in different landuse that consist of forest, agricultural land (moor land, cacao plantations, intensive and conservation annual crops), and green open space areas. The results showed that: a) forest conversion into agricultural land led to the decline of soil quality such as decreased levels of soil organic matter, soil porosity and distribution of soil pores so that the conversion of forest land into agricultural land decreases the soil hydraulic conductivity of both for the initial value and saturated hydraulic conductivity; b) forets canopy cover density affects the soil quality and soil hydraulics conductivity, where high canopy cover has the higher value of soil hydraulics conductivity compared to medium and low canopy forest; c) Situgede tourism forest has the lowest soil hydraulics conductivity compared to other forest types; d) soil hydraulics conductivity in conservation annual crops is higher than intensive annual crops land and Situgede tourism forest and it’s not significantly different from the soil hydraulics conductivity in low canopy forest; and e) soil hydraulics conductivity in green open spaces area were strongly determined by the naturalness of landscape and human intervention level on its formation and management, where the UI city forest and Lembah Gurame city park which were function as ecotourism areas has the lower soil hydraulics conductivity compared to great forest park.